Analisis Personal Branding Suwardi “Becak Lawu” sebagai Petarung MMA Indonesia ditinjau melalui Dramaturgi - Priscillia, Bernice; Setiawan, Albert Octavio (Universitas Islam Balitar, 2024)
Suwardi sees MMA as having an attraction and a desire to develop the potential of Indonesian athletes to compete in One Pride and even go international. Suwardi's self-actualization is built through his personal Instagram social media. This research aims to determine the impression management carried out by Indonesian MMA fighter Suwardi